The Construction of Internal Control System of SimaVillage in Majapahit Empire Based on Jedong Inscription IX-X - Satrio, Ragil; Sukoharsono, Eko Ganis; Prihatiningtyas, Yeney Widya (Journal of Accounting and Business Education, 2018)
This study aims to understand how internal control system in Sima village in Majapahit Empire was built based on Jedong Inscription IX-X. This research is a case study employing historical approach through interpretation of interviews, observation, and documentation. The results of this study indicate that the control environment in the village of Sima was formed through a series of preparatory ceremonies of Manusuk Sima, the use of inscription as a form of risk assessment, the ceremony of Manusuk Sima as the core control of the village of Sima, Asuji and Caitra grand celebration as a form of information and communication and renewal of the inscription as a form of monitoring the Sima. The overall internal control system existing in Majapahit Empire during Hayam Wurukâs reign was an implication of Nawa Sanga, the form of beliefs who prefer spirituality in running the government system.